GDF8 Promotes the Cell Invasiveness in Human Trophoblasts by Upregulating the Expression of Follistatin-Like 3 Through the ALK5-SMAD2/3 Signaling Pathway - Xie, Jiamin; Zhu, Hua; Chang, Hsun-Ming; Klausen, Christian; Dong, Minyue; Leung, Peter C. K. (Frontiers in Cell and Developmental Biology, 2020)
Growth differentiation factor 8 (GDF8) and its antagonist follistatin-like 3 (FSTL3) are expressed in the placenta during early pregnancy. These two factors may have a role to play in the regulation of normal placentation. However, whether GDF8 can regulate the expression of FSTL3 in human trophoblasts remains to be elucidated. In this study, we aimed to investigate the effects of GDF8 on the expression of FSTL3 and the underly-ing molecular mechanisms using human trophoblasts as a study model. Our results showed that GDF8 significantly upregulates the expression and production of FSTL3, which further promotes cell invasiveness in immortalized extravillous cytotrophoblast cells and primary extravillous cytotrophoblast cells obtained from human first-trimester placentae. Additionally, using an siRNA-mediated knockdown approach, we found that this regulatory effect is most likely mediated by the ALK5-SMAD2/3-induced signaling pathway. These findings deepen our understanding of the functional roles of GDF8 and FSTL3 in the regulation of cell invasiveness of trophoblasts.